Electrosynthesis of high-entropy metallic glass nanoparticles for designer, multi-functional electrocatalysis - Matthew W. Glasscott (Nature Portfolio, 2019)
High-entropy metallic glasses are an unexplored class of nanomaterials and are difficult to prepare. Here, the authors present an electrosynthetic method to design these materials with up to eight tunable metallic components and show multifunctional electrocatalytic water splitting capabilities.